E2F-1 regulation by an unusual DNA damage-responsive DP partner subunit. - Ingram, L; Munro, S; Coutts, A; La Thangue, N (2011)
E2F activity is negatively regulated by retinoblastoma protein (pRb) through binding to the E2F-1 subunit. Within the E2F heterodimer, DP proteins are E2F partner subunits that allow proper cell cycle progression. In contrast to the other DP proteins, the newest member of the family, DP-4, downregulates E2F activity. In this study we report an unexpected role for DP-4 in regulating E2F-1 activity during the DNA damage response. Specifically, DP-4 is induced in DNA-damaged cells, upon which it binds to E2F-1 as a non-DNA-binding E2F-1/DP-4 complex. Consequently, depleting DP-4 in cells re-instates E2F-1 activity that coincides with increased levels of chromatin-bound E2F-1, E2F-1 target gene expression and associated apoptosis. Mutational analysis of DP-4 highlighted a C-terminal region, outside the DNA-binding domain, required for the negative control of E2F-1 activity. Our results define a new pathway, which acts independently of pRb and through a biochemically distinct mechanism, involved in negative regulation of E2F-1 activity.